Development of Science Learning Media Assisted by Ethno-Vlog Sisingaan and Gembyung Dance to Improve Creative Thinking Skills - Nyi Mas Ayu Ratna Gumilar; Sudarmin; Putut Marwoto (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to develop a product in the form of Ethno-Vlog learning media for Class IV SD science learning as an effort to improve students' creative thinking skills. The Ethno-Vlog learning media contains Sisingaan and Gembyung dance with style and motion material content. This research uses the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). Thus the realization of the purpose of this research is to determine the feasibility test of the media, the practicality test, and the effectiveness of using Ethno-Vlog learning media. The development of learning media based on Ethno-Vlog Sisingaan and Gembyung dance for grade IV SD obtained the proper category from the two validators. The results of the student response questionnaire on the small-scale test were 90% and the response questionnaire from the teacher obtained 86% results indicating that learning media was very feasible to use. As for the effectiveness of using Ethno-Vlog-based learning media in improving creative thinking skills, the results are 0.60 in the moderate or effective category. The media is following the objectives of learning practices in the Independent Curriculum as well as efforts to shape the character of students and develop creative thinking skills contained in one of the dimensions of the Pancasila learner profile.